(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Chikungunya virus was introduced into the Dhaka city of Bangladesh and triggered a massive outbreak which affected millions of lives and forced upon significant damages in socioeconomic factors. Objectives: This community based descriptive study was conducted in selected area of Dhaka city to see the clinical profiles of chikungunya patients in Dhaka city. Methodology: This prospective observational study was carried out in the Department of Medicine OPD at Shaheed Suhrawardy Medical College & Hospital (ShSMC), Dhaka, Bangladesh. This cross-sectional study was conducted during the peak of chikungunya outbreak (1st March to 31st August, 2018) to document the clinical profiles of confirmed cases (laboratory test positive) and probable cases diagnosed by medical practitioners. Results: The study included 1133 patients (Male 51.9%and Female 48.1%). The main symptoms were Fever (66%), higher in patients with Joint pain (82%), Rash (21.3%) and others (10.1%).Sensitivity of the patients by acute chikungunya 14.3% and other 85.7%. Patients had post chikungunya complications 14.3% and no complications 85.7%. Chikungunya patients increasing month are March 0.5%, April 0.5%, May 3.4%, June 25.8%, July 50.8%, August 19.1%. In Dhaka cities the affected area were Mirpur 41.7%, Mohammadpur 28.9%, Agargaon 8.8%, Tejgoan 5.9%, Shamoly 5.7%, Adabar 4.4%, Savar 2.0%, Rayerbazar 0.9%, Dhanmondi 0.8%, Mohakhali 0.8%. Conclusions: The result found that gender and age are significantly associated with Chikungunya infection. This study will also help to provide support and services to public health science which will eventually contribute the country for the diagnosis, prevention and control of Chikungunya and similar viral diseases. Overall, it necessitates the importance of utilizing appropriate and reliable diagnostic methods, proper surveillance system and effective control measures that must be implemented to manage the disease outbreak situations. Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 148-151